The Analysis of the Factors Influencing Smallholder Decision on Conversion of Rubber Area into Oil Palm in Asahan District : (Case Study: Aek Songsongan Sub-District, Asahan District) - Arifin, Sofyan; Syahbuddin, Syahbuddin; Zen, Zahari (JURNAL AGRICA, 2024)
Within 10 years period from 2012 to 2021 there has been a decrease in the area of ​​smallholder rubber plantations in Asahan District by 2,918.85 Ha, while the area of ​​smallholder oil palm plantations has increased by 3,088.21 Ha. During the same period, the area of ​​smallholder rubber plantations in Aek Songsongan Sub District decreased by 985.58 Ha, while the area of ​​smallholder oil palm plantations increased by 690.00 Ha, this was due to the conversion of crops from rubber to oil palm. This research aims to determine whether the growers' decision to convert smallholder rubber plantations to oil palm is logical or profitable, and to analyze the factors that influence the conversion. Data analysis uses 2 methods, namely Partial Budgeting Analysis with 27 samples and Linear Regression Analysis with 42 samples. From the results of the analysis it is known that the farmer's decision to convert rubber plantations into oil palm is logical, this is evident from the results of the partial budgeting analysis which states that the results are profitable. The results of multiple linear regression analysis state that the influencing factors are the number of family dependents, land area before conversion and other sources of income, all three of which simultaneously influenced the conversion of 50.5%.